Mengidentifikasi Sumber Daya Manusia di SMP Negeri 8 Tidore Kepulauan untuk Meningkatkan Produktivitas Kerja - Intan Umull Magfira Sary; Agung Winarno (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze the organizational structure, roles and duties of educators and obstacles in developing human resources at SMPN 8 Tidore. The method used is descriptive research with a qualitative approach, through interviews, observations, and document analysis. The results of the study indicate that the school's organizational structure is imperfect in the division of tasks and responsibilities, which has an impact on the effectiveness of communication and coordination. Several positions are filled without considering appropriate qualifications, resulting in a lack of efficiency in human resource management. In addition, this study identified various obstacles in developing educators, including budget constraints, lack of technology training, and low public interest in becoming educators due to uncompetitive salaries compared to the rapidly growing mining sector in North Maluku. Limited infrastructure, such as unstable internet networks and electricity supplies, also hinders the implementation of technology-based curriculum. Therefore, strategic policies are needed to improve the quality of education through improving the organizational structure, improving teacher welfare, and strengthening educational support facilities. Keywords: Identifying, Human Resources, Work Productivity